A Case of Humidifier Lung Characterized by Histopathologic Feature - Saizyo, Masao; Shiota, Satomi; Nagayama, Takehisa; Sakamoto, Kyoichi; Nakaya, Yoshiaki; Iwase, Akihiko; Aoki, Shigeyuki; Kawabata, Yoshinori; Matsuoka, Rokuro (Nihon Kyōbu Shikkan Gakkai zasshi, 1997)
A 61-year-old man was discharged from our hospital after recovering from bilateral fractures in the neck of each femur. However, a productive cough, dyspnea, and a high grade fever occurred eight hours after returning home. He was thus admitted once more. At rehospitalization, there was radiographic evidence of bilateral infiltrates and hypoxemia. Hypersensitivity pneumonitis was strongly suggested by radiographic evidence, by the fact that no new drugs had been administered, and by a positive result after an environmental provocation test. A diagnosis of humidifier lung was confirmed by a positive precipitins test for humidifier water. Several microorganisms were isolated from humidifier water, and precipitins tests for the isolated microorganisms were mostly positive. Microscopic examination revealed focal alveolitis, bronchiolitis, and perivasculitis. Perivascular leucocytic infiltrations around venules suggested that inhaled antigens might have also caused humidifier lung via a vascular route. Humidifier lung may be due in part to soluble factors, such as endotoxin, present in humidifier water.